Application of Lean Six Sigma Method in Hospital Management Process: Performance Optimization and Waste Reduction - Wendra Afriana; Febriyanti Zulyani; Tikkyrino Kurniawan (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
In the dynamic environment of healthcare, hospital management constantly seeks methods to enhance performance and reduce inefficiencies. This study explores the implementation of the Lean Six Sigma (LSS) methodology in hospital management to optimize performance and minimize waste. Lean Six Sigma, a combination of Lean management and Six Sigma, is renowned for its systematic, data-driven approach in improving process efficiency and quality. We conducted a comprehensive analysis in a tertiary care hospital, employing LSS tools such as DMAIC (Define, Measure, Analyze, Improve, Control) framework, value stream mapping, and root cause analysis. The study focused on critical areas such as patient flow, inventory management, and operational processes. Our findings reveal significant improvements in patient wait times, reduction in inventory costs, and enhanced operational efficiency. The application of LSS led to a more patient-centric approach, streamlined processes, and a culture of continuous improvement within the hospital. This research contributes to the growing body of knowledge on LSS in healthcare and provides a practical framework for hospital administrators seeking to implement efficiency-enhancing strategies.